Representasi Kegiatan Ekstrakurikuler Kaligrafi Dalam Menguatkan Keterampilan Menulis Al-Qur’an - Pendi Khoer Ependi; Iqbal Ansari Mumtaz (Prodi PAI IAILM Suryalaya, 2024)
Extracurricular activities are additional activities outside class hours which aim to develop students' interests, talents and skills in various fields. The aim of this research is to determine the influence of calligraphy extracurriculars on Al-Qur'an writing skills at MTs Darul Amira Cihaurbeuti. The research method used is a descriptive method with a quantitative approach. Data collection techniques use observation, questionnaires and documentation. The result of study shows that students' ability to write calligraphy is in a good classification. Al-Qur'an Writing Skills at MTs Darul Amira Cihaurbeuti which is in the good classification with a calculated average of 80,93.2. The influence of calligraphy extracurricular activities on Al-Qur'an writing skills at MTs Darul Amira Cihaurbeuti is 45.5%. And the remaining 54.5% is influenced by other variables outside this research, including internal factors such as physical condition, intelligence, talents and interests of students as well as external factors such as the students' environment. This research was also proven by testing the hypothesis with the t test, and produced a of 4,539 > 2,048. So it can be concluded that Ho was rejected and Ha was accepted, which means that there is a positive and significant influence of calligraphy extracurricular activities (X) on Al-Qur'an writing skills at MTs Darul Amira (Y).